Urban planning – architectural report on thermal stress in the city of Madrid - Torrego Gómez, Daniel (Zenodo, 2021)
This report serves the EmCliC research project ( Embodying Climate Change ) as an analysis on the influence of architecture and urban planning on the experiences of thermal stress in the city of Madrid. It reviews the existing bibliography on the role of the urban fabric on the Urban Heat Island effect, with special focus on the different building typologies, construction solutions, materials, urban blue infrastructure or presence of green areas. This work, in addition, aims to offer a broad vision that is not restricted to the technical, but that values social, political and cultural issues as relevant elements when analyzing the relationship of the architecture of the city with overheating and, consequently, with the Climate Change. Thermal performance of the city, is integrated in this study in a broader ecosystem of interests, policies, regulations and projects, as well as in its “built” history. With that goal, the analysis focuses on the situated and embodied experiences of thermal stress, from the point of view of architecture and urban planning. The object of study, therefore, will be the Urban Heat Island (UHI). The methodology will be to reinterpret the UHI of Madrid, basing on the given cartographies, but attending to more specific and embodied conditions. Therefore, the UHI will not be only be analyzed as a shape that covers the city, but as something more concrete, that is dependent on specific and situated assemblages of heterogeneous phenomena such as urban density, presence -or absence- of air currents, thermal buffers, radiant surfaces, the actions of neighbors, or bioclimatic ordinances. : The Embodying Climate Change project is funded by Iceland, Liechtenstein and Norway through the EEA Grants. : {"references": ["Badarnah, L., & Knaack, U. (2008). Organizational features in leaves for application in shading systems for building envelopes. WIT Trans. Ecol. Environ, 114, 87-96. Barral, B. C. (2015). El Madrid burgu\u00e9s: el ensanche Este de la capital,(1860-1931) (Doctoral dissertation, Universidad Complutense de Madrid). Basu, R. (2009). High ambient temperature and mortality: a review of epidemiologic studies from 2001 to 2008. Environmental health, 8(1), 1-13. BOE, Bolet\u00edn Oficial del Estado, Gobierno de Espa\u00f1a (2021). Ley 7/2021, de 20 de mayo, de cambio clim\u00e1tico y transici\u00f3n energ\u00e9tica. BOE, Bolet\u00edn Oficial del Estado, Real Decreto Legislativo 7/2015, de 30 de octubre, por el que se aprueba el texto refundido de la Ley de Suelo y Rehabilitaci\u00f3n Urbana. Borrallo-Jim\u00e9nez, M., LopezDeAsiain, M., Esquivias, P. M., & Delgado-Trujillo, D. (2021). Comparative study between the passive house standard in warm climates and nearly zero energy buildings under spanish technical building code in a dwelling design in seville, spain. Energy and Buildings, 111570. Cervero S\u00e1nchez, N., & Agust\u00edn-Hern\u00e1ndez, L. (2018). Evaluaci\u00f3n gr\u00e1fica de la rehabilitaci\u00f3n urbana del poblado dirigido de Ca\u00f1o Roto. Chumillas, I. R. (2001). Vivienda y promoci\u00f3n inmobiliaria en Madrid (Vol. 43). Universitat de Lleida. C\u00f3rdoba-Hern\u00e1ndez, R., Carmona-Mateos, F., \u00c1lvarez, D. M., Rom\u00e1n-L\u00f3pez, E., & S\u00e1nchez-Guevara, C. \u00c1rea de Regeneraci\u00f3n Urbana Ciudad de los \u00c1ngeles de Madrid. Ciudad y Territorio Estudios Territoriales (CyTET), 52(204), 349-356. C. T. E. C\u00f3digo T\u00e9cnico de la Edificaci\u00f3n(2019). Documento B\u00e1sico Ahorro de Energ\u00eda HE1: Limitaci\u00f3n de la Demanda Energ\u00e9tica. Madrid. December. Cuerda, E., P\u00e9rez, M., & Neila, J. (2014). Facade typologies as a tool for selecting refurbishment measures for the Spanish residential building stock. Energy and Buildings, 76, 119-129. Esteban-Maluenda, A. M. (2000). Madrid, a\u00f1os 50: La investigaci\u00f3n en torno a la vivienda social. Los poblados dirigidos. Fanger, P. O. (1970). Thermal comfort. Analysis and applications in environmental engineering. Thermal comfort. Analysis and applications in environmental engineering. Fern\u00e1ndez, F., Allende, F., Rasilla, D. Martilli, A.,Alcaide, J. (2016). Estudio de Detalle del Clima Urbano de Madrid. Universidad Aut\u00f3noma de Madrid, Aynutamiento de Madrid. Fernandez-Antolin, M. M., del R\u00edo, J. M., Costanzo, V., Nocera, F., & Gonzalez-Lezcano, R. A. (2019). Passive design strategies for residential buildings in different Spanish climate zones. Sustainability, 11(18), 4816. Fern\u00e1ndez Garcla, F., L\u00f3pez G\u00f3mez, A., & L\u00f3pez G\u00f3mez, A. (1996). La influencia del relieve en la isla de calor de Madrid: las vaguadas del Manzanares y del Abro\u00f1igal. Estudios Geogr\u00e1ficos, 57(224), 473\u2013494. https://doi.org/10.3989/egeogr.1996.i224.682 Fern\u00e1ndez Nieto, M. A. (2006). Las colonias del hogar del empleado: la periferia como ciudad (Doctoral dissertation, Arquitectura). Rubio, F. D., & Fogu\u00e9, U. (2015). Unfolding the political capacities of design. eScholarship, University of California. Gunawardena, K. R., Wells, M. J., & Kershaw, T. (2017). Utilising green and bluespace to mitigate urban heat island intensity. Science of the Total Environment, 584, 1040-1055. Hern\u00e1ndez, A., Su\u00e1rez, C. and Zuli, M., (2021). \u00bfDe qu\u00e9 a\u00f1o es tu casa? El mapa que muestra c\u00f3mo se ha construido Espa\u00f1a. [online] Elconfidencial.com. Available at: [Accessed 11 June 2021]. Higueras Garc\u00eda, Ester (2009). \"La ordenanza bioclim\u00e1tica de Tres Cantos, Madrid. \u00daltimos avances en planificaci\u00f3n ambiental y sostenible.\" Revista de Urbanismo 20. Humphreys, M. (1978). Outdoor temperatures and comfort indoors. Batiment International, Building Research and Practice, 6(2), 92-92. JAQUE, A. J. (2011). Eco-ordinary: etiquetas para la pr\u00e1ctica cotidiana de la arquitectura= Eco-ordinary: codes for everyday architectural practices/Eco-ordinary. Oficina de Innofaci\u00f3n Pol\u00edtica Universidad Europea de Madrid. Khomenko, S., Cirach, M., Pereira-Barboza, E., Mueller, N., Barrera-G\u00f3mez, J., Rojas-Rueda, D., ... & Nieuwenhuijsen, M. (2021). Premature mortality due to air pollution in European cities: A health impact assessment. The Lancet Planetary Health, 5(3), e121-e134. Larriva, M. T. B., & Higueras, E. (2020). Health risk for older adults in Madrid, by outdoor thermal and acoustic comfort. Urban Climate, 34, 100724. De Lux\u00e1n, M., & G\u00f3mez, G. (2006). Dos bloques de viviendas y locales comerciales en San Crist\u00f3bal de los \u00c1ngeles, Madrid. Informes de la Construcci\u00f3n, 58(502), 5-16. De Lux\u00e1n, M. V\u00e1zquez, M., Rom\u00e1n, E., & Barbero, M. (2008). Criterios de sostenibilidad para la rehabilitaci\u00f3n privada de viviendas en los barrios de Hortaleza, Jacinto Benavente, y sector 1 de Lavapi\u00e9s de Madrid. Empresa Municipal de la Vivienda, Madrid. L\u00f3pez G\u00f3mez, A., L\u00f3pez G\u00f3mez, J., Fern\u00e1ndez Garc\u00eda, F., & Arroyo Ilera, F. (1988). El Clima urbano de Madrid: La isla de calor. Madrid: CSIC de Lucio, R. L. (2017). El \"Ecobulevar\" del PAU de Vallecas, 1995-2016 Un caso paradigm\u00e1tico de fracaso del planeamiento y el dise\u00f1o urbanos y de la arquitectura| The 'Eco-boulevard'of the Vallecas Urban Action Programme, 1995\u20132016 A paradigmatic case of the failure of urban planning, urban design and architecture. ZARCH, (8), 42-61. Madrid, Ayuntamiento de (2009). Buenas pr\u00e1cticas en arquitectura y urbanismo para Madrid. Criterios bioclim\u00e1ticos y de eficiencia energ\u00e9tica. \u00c1rea de Gobierno de Urbanismo y Vivienda. Subdirecci\u00f3n General de Planificaci\u00f3n General y Periferia Urbana. Madrid, Ayuntamiento de (2013) Revisi\u00f3n del Plan General, Informe de sostenibilidad ambiental. Area de Gobierno de Urbanismo y Vivienda. Madrid, Ayuntamiento de (2018) Plan Regenera, Mad-Re. \u00c1rea de Gobierno de Desarrollo Urbano Sostenible. Direcci\u00f3n General de Planificaci\u00f3n Estrat\u00e9gica Madrid, Ayuntamiento de (2020). LA ISLA DE COLOR. Las infraestructuras verdes como oportunidad estrat\u00e9gica en el modelo de ciudad. \u00c1rea de Gobierno de Desarrollo Urbano. Direcci\u00f3n General de Planificaci\u00f3n Estrat\u00e9gica. Madrid, Comunidad de (2019). Vigilancia y control de los efectos de las olas de calor 2019. Plan de respuesta ante los riesgos. Direcci\u00f3n General de Salud P\u00fablica Mart\u00edn-Consuegra, F., de Frutos, F., Oteiza, I., & Agust\u00edn, H. A. (2018). Use of cadastral data to assess urban scale building energy loss. Application to a deprived quarter in Madrid. Energy and Buildings, 171, 50-63. Mueller, N., Rojas-Rueda, D., Khreis, H., Cirach, M., Andr\u00e9s, D., Ballester, J., ... & Nieuwenhuijsen, M. (2020). Changing the urban design of cities for health: The superblock model. Environment international, 134, 105132. Nu\u00f1ez Peir\u00f3, M. N., L\u00f3pez, E. R., S\u00e1nchez, C. S. G., & Gonz\u00e1lez, F. J. N. (2016). Hacia un modelo din\u00e1mico para la isla de calor urbana de Madrid. Towards a Dynamic Model for the Urban Heat Island of Madrid. Anales de edificaci\u00f3n, 2(1), 49-58. N\u00fa\u00f1ez Peir\u00f3, M., S\u00e1nchez-Guevara S\u00e1nchez, C., & Neila Gonz\u00e1lez, F. J. (2017). Actualizaci\u00f3n de la isla de calor urbana de Madrid y su influencia en la simulaci\u00f3n energ\u00e9tica de edificios. In Proceedings of the 3rd International Congress on Sustainable Construction and Eco-Efficient Solutions.(2017), p 890-901. Universidad de Sevilla. Escuela T\u00e9cnica Superior de Arquitectura.. Pombo, O., Rivela, B., & Neila, J. (2014). Modelo de edificaci\u00f3n para el an\u00e1lisis multicriterio de la rehabilitaci\u00f3n del parque residencia madrile\u00f1o de los a\u00f1os 1950-1980. Archit. Res. Find. Build. Constr. Manag. Technol., Escuela T\u00e9cnica Superior de Arquitectura de Madrid, Madrid, 412-416. Salamanca, F., Martilli, A., & Yag\u00fce, C. (2012). A numerical study of the Urban Heat Island over Madrid during the DESIREX (2008) campaign with WRF and an evaluation of simple mitigation strategies. International Journal of Climatology, 32(15), 2372-2386. Sambricio, C. (Ed.). (2003). Un siglo de vivienda social: 1903-2003. Madrid: Nerea. S\u00e1nchez, C. S. G., Mavrogianni, A., & Gonz\u00e1lez, F. J. N. (2017). On the minimal thermal habitability conditions in low income dwellings in Spain for a new definition of fuel poverty. Building and Environment, 114, 344-356. Shishegar, N. (2015) The Impact of Green Areas on Mitigating Urban Heat Island Effect: A Review. The International Journal of Environmental Sustainability, Vol. 9, Issue 1, 119-130 Thorsson, Sofia, et al. \"POTENTIAL INCREASE IN HEAT STRESS IN SWEDISH CITIES DUE TO CLIMATE CHANGE: THE IMPACT OF BUILT STRUCTURE ON THERMAL COMFORT.\" The seventh International Conference on Urban Climate, Yokohama, Japan. 2009. Tumini, I. (2013). El microclima urbano en los espacios abiertos: estudio de casos en Madrid (Doctoral dissertation, Arquitectura). Varela, S., Vi\u00f1as, C., Rodr\u00edguez, A., & Aguilera, P. (2018). Analysis of the thermal behaviour of the ETICS system: Rehabilitated building in Madrid. Anales de Edificaci\u00f3n, 4(4), 35-41.", "Barral, B. C. (2015). El Madrid burgu\u00e9s: el ensanche Este de la capital,(1860-1931) (Doctoral dissertation, Universidad Complutense de Madrid).", "Basu, R. (2009). High ambient temperature and mortality: a review of epidemiologic studies from 2001 to 2008. Environmental health, 8(1), 1-13.", "BOE, Bolet\u00edn Oficial del Estado, Gobierno de Espa\u00f1a (2021). Ley 7/2021, de 20 de mayo, de cambio clim\u00e1tico y transici\u00f3n energ\u00e9tica.", "BOE, Bolet\u00edn Oficial del Estado, Real Decreto Legislativo 7/2015, de 30 de octubre, por el que se aprueba el texto refundido de la Ley de Suelo y Rehabilitaci\u00f3n Urbana.", "Borrallo-Jim\u00e9nez, M., LopezDeAsiain, M., Esquivias, P. M., & Delgado-Trujillo, D. (2021). Comparative study between the passive house standard in warm climates and nearly zero energy buildings under spanish technical building code in a dwelling design in seville, spain. Energy and Buildings, 111570.", "Cervero S\u00e1nchez, N., & Agust\u00edn-Hern\u00e1ndez, L. (2018). Evaluaci\u00f3n gr\u00e1fica de la rehabilitaci\u00f3n urbana del poblado dirigido de Ca\u00f1o Roto.", "Chumillas, I. R. (2001). Vivienda y promoci\u00f3n inmobiliaria en Madrid (Vol. 43). Universitat de Lleida.", "C\u00f3rdoba-Hern\u00e1ndez, R., Carmona-Mateos, F., \u00c1lvarez, D. M., Rom\u00e1n-L\u00f3pez, E., & S\u00e1nchez-Guevara, C. \u00c1rea de Regeneraci\u00f3n Urbana Ciudad de los \u00c1ngeles de Madrid. Ciudad y Territorio Estudios Territoriales (CyTET), 52(204), 349-356.", "C. T. E. C\u00f3digo T\u00e9cnico de la Edificaci\u00f3n(2019). Documento B\u00e1sico Ahorro de Energ\u00eda HE1: Limitaci\u00f3n de la Demanda Energ\u00e9tica. Madrid. December.", "Cuerda, E., P\u00e9rez, M., & Neila, J. (2014). Facade typologies as a tool for selecting refurbishment measures for the Spanish residential building stock. Energy and Buildings, 76, 119-129.", "Esteban-Maluenda, A. M. (2000). Madrid, a\u00f1os 50: La investigaci\u00f3n en torno a la vivienda social. Los poblados dirigidos.", "Fanger, P. O. (1970). Thermal comfort. Analysis and applications in environmental engineering. Thermal comfort. Analysis and applications in environmental engineering.", "Fern\u00e1ndez, F., Allende, F., Rasilla, D. Martilli, A.,Alcaide, J. (2016). Estudio de Detalle del Clima Urbano de Madrid. Universidad Aut\u00f3noma de Madrid, Aynutamiento de Madrid.", "Fern\u00e1ndez, F., Allende, F., Rasilla, D. Martilli, A.,Alcaide, J. (2016). Estudio de Detalle del Clima Urbano de Madrid. Universidad Aut\u00f3noma de Madrid, Aynutamiento de Madrid.", "Fern\u00e1ndez Garcla, F., L\u00f3pez G\u00f3mez, A., & L\u00f3pez G\u00f3mez, A. (1996). La influencia del relieve en la isla de calor de Madrid: las vaguadas del Manzanares y del Abro\u00f1igal. Estudios Geogr\u00e1ficos, 57(224), 473\u2013494. https://doi.org/10.3989/egeogr.1996.i224.682", "Fern\u00e1ndez Nieto, M. A. (2006). Las colonias del hogar del empleado: la periferia como ciudad (Doctoral dissertation, Arquitectura).", "Rubio, F. D., & Fogu\u00e9, U. (2015). Unfolding the political capacities of design. eScholarship, University of California.", "Gunawardena, K. R., Wells, M. J., & Kershaw, T. (2017). Utilising green and bluespace to mitigate urban heat island intensity. Science of the Total Environment, 584, 1040-1055.", "Hern\u00e1ndez, A., Su\u00e1rez, C. and Zuli, M., (2021). \u00bfDe qu\u00e9 a\u00f1o es tu casa? El mapa que muestra c\u00f3mo se ha construido Espa\u00f1a. [online] Elconfidencial.com. Available at: [Accessed 11 June 2021].", "Higueras Garc\u00eda, Ester (2009). \"La ordenanza bioclim\u00e1tica de Tres Cantos, Madrid. \u00daltimos avances en planificaci\u00f3n ambiental y sostenible.\" Revista de Urbanismo 20.", "Humphreys, M. (1978). Outdoor temperatures and comfort indoors. Batiment International, Building Research and Practice, 6(2), 92-92.", "JAQUE, A. J. (2011). Eco-ordinary: etiquetas para la pr\u00e1ctica cotidiana de la arquitectura= Eco-ordinary: codes for everyday architectural practices/Eco-ordinary. Oficina de Innofaci\u00f3n Pol\u00edtica Universidad Europea de Madrid.", "Khomenko, S., Cirach, M., Pereira-Barboza, E., Mueller, N., Barrera-G\u00f3mez, J., Rojas-Rueda, D., ... & Nieuwenhuijsen, M. (2021). Premature mortality due to air pollution in European cities: A health impact assessment. The Lancet Planetary Health, 5(3), e121-e134.", "Larriva, M. T. B., & Higueras, E. (2020). Health risk for older adults in Madrid, by outdoor thermal and acoustic comfort. Urban Climate, 34, 100724.", "De Lux\u00e1n, M., & G\u00f3mez, G. (2006). Dos bloques de viviendas y locales comerciales en San Crist\u00f3bal de los \u00c1ngeles, Madrid. Informes de la Construcci\u00f3n, 58(502), 5-16.", "De Lux\u00e1n, M. V\u00e1zquez, M., Rom\u00e1n, E., & Barbero, M. (2008). Criterios de sostenibilidad para la rehabilitaci\u00f3n privada de viviendas en los barrios de Hortaleza, Jacinto Benavente, y sector 1 de Lavapi\u00e9s de Madrid. Empresa Municipal de la Vivienda, Madrid.", "L\u00f3pez G\u00f3mez, A., L\u00f3pez G\u00f3mez, J., Fern\u00e1ndez Garc\u00eda, F., & Arroyo Ilera, F. (1988). El Clima urbano de Madrid: La isla de calor. Madrid: CSIC", "de Lucio, R. L. (2017). El \"Ecobulevar\" del PAU de Vallecas, 1995-2016 Un caso paradigm\u00e1tico de fracaso del planeamiento y el dise\u00f1o urbanos y de la arquitectura| The 'Eco-boulevard'of the Vallecas Urban Action Programme, 1995\u20132016 A paradigmatic case of the failure of urban planning, urban design and architecture. ZARCH, (8), 42-61.", "Madrid, Ayuntamiento de (2009). Buenas pr\u00e1cticas en arquitectura y urbanismo para Madrid. Criterios bioclim\u00e1ticos y de eficiencia energ\u00e9tica. \u00c1rea de Gobierno de Urbanismo y Vivienda. Subdirecci\u00f3n General de Planificaci\u00f3n General y Periferia Urbana.", "Madrid, Ayuntamiento de (2013) Revisi\u00f3n del Plan General, Informe de sostenibilidad ambiental. Area de Gobierno de Urbanismo y Vivienda.", "Madrid, Ayuntamiento de (2018) Plan Regenera, Mad-Re. \u00c1rea de Gobierno de Desarrollo Urbano Sostenible. Direcci\u00f3n General de Planificaci\u00f3n Estrat\u00e9gica", "Madrid, Ayuntamiento de (2020). LA ISLA DE COLOR. Las infraestructuras verdes como oportunidad estrat\u00e9gica en el modelo de ciudad. \u00c1rea de Gobierno de Desarrollo Urbano. Direcci\u00f3n General de Planificaci\u00f3n Estrat\u00e9gica.", "Madrid, Comunidad de (2019). Vigilancia y control de los efectos de las olas de calor 2019. Plan de respuesta ante los riesgos. Direcci\u00f3n General de Salud P\u00fablica", "Mart\u00edn-Consuegra, F., de Frutos, F., Oteiza, I., & Agust\u00edn, H. A. (2018). Use of cadastral data to assess urban scale building energy loss. Application to a deprived quarter in Madrid. Energy and Buildings, 171, 50-63.", "Mueller, N., Rojas-Rueda, D., Khreis, H., Cirach, M., Andr\u00e9s, D., Ballester, J., ... & Nieuwenhuijsen, M. (2020). Changing the urban design of cities for health: The superblock model. Environment international, 134, 105132.", "Nu\u00f1ez Peir\u00f3, M. N., L\u00f3pez, E. R., S\u00e1nchez, C. S. G., & Gonz\u00e1lez, F. J. N. (2016). Hacia un modelo din\u00e1mico para la isla de calor urbana de Madrid. Towards a Dynamic Model for the Urban Heat Island of Madrid. Anales de edificaci\u00f3n, 2(1), 49-58.", "N\u00fa\u00f1ez Peir\u00f3, M., S\u00e1nchez-Guevara S\u00e1nchez, C., & Neila Gonz\u00e1lez, F. J. (2017). Actualizaci\u00f3n de la isla de calor urbana de Madrid y su influencia en la simulaci\u00f3n energ\u00e9tica de edificios. In Proceedings of the 3rd International Congress on Sustainable Construction and Eco-Efficient Solutions.(2017), p 890-901. Universidad de Sevilla. Escuela T\u00e9cnica Superior de Arquitectura..", "Pombo, O., Rivela, B., & Neila, J. (2014). Modelo de edificaci\u00f3n para el an\u00e1lisis multicriterio de la rehabilitaci\u00f3n del parque residencia madrile\u00f1o de los a\u00f1os 1950-1980. Archit. Res. Find. Build. Constr. Manag. Technol., Escuela T\u00e9cnica Superior de Arquitectura de Madrid, Madrid, 412-416.", "Salamanca, F., Martilli, A., & Yag\u00fce, C. (2012). A numerical study of the Urban Heat Island over Madrid during the DESIREX (2008) campaign with WRF and an evaluation of simple mitigation strategies. International Journal of Climatology, 32(15), 2372-2386.", "Sambricio, C. (Ed.). (2003). Un siglo de vivienda social: 1903-2003. Madrid: Nerea.", "S\u00e1nchez, C. S. G., Mavrogianni, A., & Gonz\u00e1lez, F. J. N. (2017). On the minimal thermal habitability conditions in low income dwellings in Spain for a new definition of fuel poverty. Building and Environment, 114, 344-356.", "Shishegar, N. (2015) The Impact of Green Areas on Mitigating Urban Heat Island Effect: A Review. The International Journal of Environmental Sustainability, Vol. 9, Issue 1, 119-130", "Thorsson, Sofia, et al. \"POTENTIAL INCREASE IN HEAT STRESS IN SWEDISH CITIES DUE TO CLIMATE CHANGE: THE IMPACT OF BUILT STRUCTURE ON THERMAL COMFORT.\" The seventh International Conference on Urban Climate, Yokohama, Japan. 2009.", "Tumini, I. (2013). El microclima urbano en los espacios abiertos: estudio de casos en Madrid (Doctoral dissertation, Arquitectura).", "Varela, S., Vi\u00f1as, C., Rodr\u00edguez, A., & Aguilera, P. (2018). Analysis of the thermal behaviour of the ETICS system: Rehabilitated building in Madrid. Anales de Edificaci\u00f3n, 4(4), 35-41."]}